PROGRAM PEMBERDAYAAN MASYARAKAT POLA BISNIS DIGITAL DALAM MENDORONG UMKM KUE BASAH DI DESA ANGGASWANGI KABUPATEN SIDOARJO - fitryani fitryani; Aditya Surya Nanda (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Researchers provide solutions in encouraging the growth of this cake business by providing some good feedback. The first is to develop variants that are popular in the market, the second is to provide assistance on financial management and the third is to provide training on marketing both offline and online. Output targets are solutions to ongoing problems, scientific publications through journals with ISSN, publications in mass media, increasing the quality and quantity of business and product management, increasing the application of science and technology, and increasing the value of partners from an economic and social perspective. The method used is personal assistance to partners. The plan that will be carried out by the team is to provide training to market products, provide training on making cakes with new variants and provide assistance on good financial management of their businesses (starting from the production management process, simple bookkeeping, effective marketing and inspiring successful entrepreneurs) by bring in competent experts to boost their business. Then assist partners in marketing products offline and online so that the market reach is wider.